Perilaku Masyarakat Desa Kolongan kecamatan Talawaan Kabupaten Minahasa Utara Terhadap Penyakit Malaria di Masa Pandemi Covid-19 - Iyone Esra Tiurma Siagian; Victor D. Pijoh; Grace Lendawati Amelia (Bioveritas Journal of Biology, 2022)
Malaria is an infectious disease that occurs throughout the world, especially in the tropics. One of the factors that cause the high incidence of malaria is the behavior of the community towards malaria. People's lives during the Covid-19 pandemic have changed a lot, especially in the field of individual hygiene and the environment. Data from the Talawaan Health Center in 2020 found 4 cases of people suffering from malaria in Talawaan District, North Minahasa Regency, which increased from 2019 with a total of only 2 cases of malaria infection. This study aims to determine the behavior of the people of Kolongan Village, Talawaan District, North Minahasa Regency, towards malaria during the Covid-19 pandemic. This study is a descriptive study that is observational in nature. The people of Kolongan Village, Talawaan District, North Minahasa Regency, have good knowledge about malaria and the signs and symptoms of malaria during the Covid-19 pandemic, but knowledge related to the malaria incubation period is still limited. Respondents' attitudes regarding malaria during the Covid-19 pandemic have been relatively good, which is shown by closing doors and windows to avoid mosquitoes from entering, maintaining environmental cleanliness for malaria prevention, and draining puddles to avoid mosquito shelters.